Health e-Cards as a Means of Encouraging Help Seeking for Depression Among Young Adults: Randomized Controlled Trial - Costin, Daniel L; Mackinnon, Andrew J; Griffiths, Kathleen M; Batterham, Philip J; Bennett, Anthony J; Bennett, Kylie; Christensen, Helen (JMIR Publications, 2009)
Background There is a need to identify interventions that increase help seeking for depression among young adults. Objective The aim was to evaluate a brief depression information intervention employing health e-cards (personalized emails containing links to health information presented on a Web page). Methods A randomized controlled trial was carried out with 348 19- to 24-year-olds drawn from the community. Participants were randomized to receive one of three conditions, all of which delivered a short series of health e-cards. Two active conditions involved the delivery of depression information designed to increase help-seeking behavior and intentions and to improve beliefs and knowledge associated with help seeking. A control arm delivered information about general health issues unrelated to depression. The primary outcome was help-seeking behavior. Secondary outcomes were help-seeking intentions; beliefs about the efficacy of depression treatments and help sources; ability to recognize depression; knowledge of the help-seeking process; and depressive symptoms. The study's primary focus was outcomes relating to formal help seeking (consultation with a general practitioner or mental health professional) but also targeted behaviors, intentions, and beliefs relating to informal help seeking. Results Relative to the control condition, depression health e-cards were not associated with an increase in formal help-seeking behavior, nor were they associated with improved beliefs about depression treatments; ability to recognize depression; knowledge of the help-seeking process; or depressive symptoms. Depression e-cards were associated with improved beliefs about the overall efficacy of formal help sources (z = 2.4, P = .02). At post-intervention, participants in all conditions, relative to pre-intervention, were more likely to have higher intentions of seeking help for depression from a formal help source (t641 = 5.8, P < .001) and were more likely to rate interpersonal psychotherapy as being helpful (z = 2.0, P = .047). Depression e-cards were not associated with any significant changes in informal help-seeking behavior, intentions, or beliefs. Conclusions The study found no evidence that providing depression information in the form of brief e-cards encourages help seeking for depression among young adults. Involvement in the study may have been associated with increased help-seeking intentions among participants in all conditions, suggesting that mechanisms other than depression information may increase help seeking. Trial Registration International Standard Randomized Controlled Trial Number (ISRCTN): ISRCTN98406912; http://www.controlled-trials.com/ISRCTN98406912/ISRCTN98406912 (Archived by WebCite at http://www.webcitation.org/5k221KiMi)